Hydroxyl-assisted selective epoxidation of perillyl alcohol with hydrogen peroxide by vanadium-substituted phosphotungstic acid hinged on imidazolyl activated carbon. (17th March 2022) - He, Huiting; Zheng, Min; Liu, Qiang; Liu, Jian; Zhao, Juan; Zhuang, Yuting; Liu, Xianxiang; Xu, Qiong; Kirk, Steven R.; Yin, Dulin
Abstract : Vanadium-substituted phosphotungstic acid hinged on imidazolyl activated carbon catalyzed efficiently and stably the selective epoxidation of perillyl alcohol with H2 O2 . Abstract : Through the amidation reaction with 2-methylimidazole, organic basic groups were introduced into the carboxyl sites of activated carbon to obtain imidazolyl activated carbon. H3+ x PW12− x V x O40 ( x = 0, 1, 2, or 3) was chemically bonded to the surface, which was used to catalyze the oxidation of perillyl alcohol by hydrogen peroxide. After reaction at 60 °C for 5 h, AC-COIMIH + [H4 PW10 V2 ] − could catalyze almost complete oxidation of the substrate, where the conversion reached 97.4%, the selectivity for the 1, 2-epoxide was 80.0%, and the stereo configuration of the epoxide product was RR / SS = 5 : 3. In addition, the catalyst could be easily recovered via centrifugation and reused five times without any significant deactivation. By calculating the Fukui function of perillyl alcohol, we consider a proper explanation for the main product from the oxidation of the allyl alcohol. A cooperative epoxidation mechanism with electrostatic adsorption of a double bond, and hydrogen-bonded adsorption of hydroxyl was proposed.